A proposed guidance program for Assumption Grade School of San Fernando, Pampanga - Yumul, Elizabeth D. (Animo Repository, 1973)
v. 1. This study proposes a guidance program for Assumption Grade School. Data were gathered from observations and interviews with the school principal and teachers which served as the bases for the listing of the problems and needs of the students. It was found that the students of Assumption Grade School have the following problems : parent-child relations, boy-girl relations, teacher-pupil relations, and academic problems. The program proposed to meet these needs included the following services : individual inventory service, information service, counseling service, placement service, and follow-up. For the proper implementation of the proposed program, it was recommended that a feasibility study be conducted aimed at surveying the needs of the students of Assumption Grade School and that modifications in the proposed services be effected based on the results of the study. It was also recommended that a furnished guidance and counseling room be provided, and that a forty-minute period once a week be set aside for group guidance. It was likewise suggested that a guidance fee be charged every student so as to help fund the guidance program. Other recommendations worthy of the administrators' attention were that the grading period be diminished from six terms to quarterly terms so as to allow time to make anecdotal records and other needed reports and that the teacher-moderators be given extra compensation for guidance services rendered. v. 2. This study aims to present a counseling theory and some techniques that will help resolve the problem of a counselee. It also aims to prove the applicability of these counseling theory and techniques to the Philippine counseling situation. The descriptive case presentation method was used. Interviews were conducted and descriptions of the same were compiled. The counselee's cumulative folder and autobiography were also major sources of information. Theoretical application was centered on the Rational-Emotive Therapy of Albert Ellis. Role playing was also utilized towards the resolution of the given problems. Varied responses and leads contributed to effecting the resolution of the identified problems. As per the counselee's verbalizations, the theory and techniques that were employed had positive results. However, the success of the counseling relationship was not attributed to the theory and techniques alone. Much of it resulted from the counselee's willingness to cooperate with the counselor. Although the theoretical orientation were centered on Rational-Emotive Therapy, the counselor's application of the same was distinct from other counselors' manner of application. This would mean tailoring of the techniques not only to the client but to the counselor as well. This study had a sole sample and no generalization was recommended. However, it was attested that the theories and techniques obtained positive results. Further application is hoped to present better evidence of their worth to the Philippine counseling situation. v. 3. This study aims to define and describe a continuum of counseling responses and leads. It also aims to demonstrate their applicability to varied situations through the examples cited and the analysis of a counseling protocol. The method utilized was library research. A synthesis of the discussions of the various counseling responses were made and two counseling simulations were recorded so that examples may be lifted from them. A protocol, taken from a real case, was analyzed in terms of the counselor's responses. The counseling responses and leads identified were the following: acceptance, restatement, reflection of feeling, interpretation, explanation, general leads, assurance-reassurance, summary, suggestion, and urging. In the counseling protocol that was analyzed, there was a prevalence of interpretations in the form of clarifications. Restatements and general leads were found in the initial and middle part of the interview, and suggestion and urging were used more often during the latter part of the interview. Acceptance was conveyed through verbal and non-verbal behavior throughout the session. A further study was suggested to investigate the responses and leads that are often used by Filipino counselors in the Philippine counseling situation. Another study was one that would augment the number of counseling responses and leads that were presented in this study.